Design rules for stiffened panel buckling containment features. (July 2017) - Houston, G.; Quinn, D.; Murphy, A.; Bron, F.
Abstract: This paper presents a method to generate design charts and preliminary design rules for the buckling behaviour of stiffened panel plate elements with buckling containment features. Two modelling approaches are used one with an analytical basis using classical plate theory and one with a numerical basis using the FEM to generate the design charts. The individual modelling approaches are used for cross verification. A novel design chart, based on key geometric ratios is introduced and its use demonstrated. Finally design chart data is explored to demonstrate the formulation of simple design rules which are appropriate for preliminary structural design. Highlights: Predictive design methods for plate elements with buckling containment features. Design methods based on both classical plate theory and Finite Element simulations. Design methods validated experimentally for wing and fuselage panel applications.